Inwestycje społeczne jako odpowiedź na prognozowane wyzwania rozwojowe regionu Dolnego Śląska. Raport z ustaleń seminarium naukowego współfinansowanego przez Samorząd Województwa Dolnośląskiego w ramach umowy nr DS-E/19/2018 - Michalewska-Pawlak, Małgorzata; Klimowicz, Monika; Moroń, Dorota (2018)
The report presents results of a multi-stage research procedure on forecasting the Lower Silesia developmental challenges as well as recommendations for social investment policy as a response to them. Foresight is the main research method presented in the report, due to its prognostic nature, which includes the formulation of probable scenarios for the future development in the process of collective reflection, based on the available data.In the first phase of foresight procedure, the social situation in Lower Silesia and the existing trends of social change were identified. At the second stage, the research team analysed the collected signals and set the main trends of change. The analysis of trends was carried out using the Delphi method. Selected trends were then used in the third stage of research, to verify their impact on the life and social situation of several groups of citizens: pupils, seniors, migrants, unemployed graduates and disabled in the perspective of the next ten years.The last, fourth stage of the research aimed to develop recommendations for the implementation of social investments in the Lower Silesia region, which may contribute to limiting the negative effects of potential social risks and increase the quality of life of Lower Silesia residents in the next ten years. Implementation of this method required not only the current data and information on social life, but also the experience and intuition of researchers undertaking efforts to diagnose the future. In addition to the involvement of scientists, bachelor, master and PhD students of the Faculty of Social Sciences at the University of Wroclaw also took part in the research.
Keywords: foresight; social investment; Lower Silesia